Vacuolating Cytotoxin A Triggers Mitophagy in Helicobacter pylori-Infected Human Gastric Epithelium Cells - Wang, Li; Yi, Juan; Yin, Xiao-Yang; Hou, Jin-Xia; Chen, Jing; Xie, Bei; Chen, Gang; Wang, Qun-Feng; Wang, Li-Na; Wang, Xiao-Yuan; Sun, Jing; Huo, Lei-Ming; et al. (Frontiers in Oncology, 2022)
Helicobacter pylori (H. pylori)-derived vacuolating cytotoxin A (VacA) causes damage to various organelles including mitochondria and induces autophagy and cell death. However, it is unknown whether VacA-induced mitochondrial damage can develop into mitophagy. In this study, we uncovered that H. pylori, H. pylori culture filtrate (HPCF), and VacA all could activate autophagy in a gastric epithelial cell line (GES-1). VacA-caused mitochondria depolarization retards the import of PINK1 on the damaged mitochondria and evokes mitophagy. And, among mass spectrometry (LC-MS/MS) identified 25 mitochondrial proteins binding with VacA, Tom20, Tom40, and Tom70, TOM complexes responsible for PINK1 import, were further identified could bind VacA in vitro using pull-down assay, co-immunoprecipitation, and protein-protein dockings. In addition, we found that the cell membrane protein STOM and the mitochondria inner membrane protein PGAM5 also interact with VacA. These findings suggest that VacA captured by STOM forms endosomes to enter cells and targets mitochondria. Then, VacA is transported into the mitochondrial membrane space through the TOM complexes, and PGAM5 aids in inserting VacA into the inner mitochondrial membrane to destroy the membrane potential, which promotes PINK1 accumulation and Parkin recruitment to induce mitophagy. This study helps us understand VacA entering mitochondria to induce the mitophagy process.